Do Wild Polar Bears (Ursus maritimus) Use Tools When Hunting Walruses (Odobenus rosmarus)? - Stirling, Ian; Laidre, Kristin L.; Born, Erik W. (ARCTIC, 2021)
Since the late 1700s, reports of polar bears (Ursus maritimus) using tools (i.e., pieces of ice or stones) to kill walruses (Odobenus rosmarus) have been passed on verbally to explorers and naturalists by their Inuit guides, based on local traditional ecological knowledge (TEK) as well as accounts of direct observations or interpretations of tracks in the snow made by the Inuit hunters who reported them. To assess the possibility that polar bears may occasionally use tools to hunt walruses in the wild, we summarize 1) observations described to early explorers and naturalists by Inuit hunters about polar bears using tools, 2) more recent documentation in the literature from Inuit hunters and scientists, and 3) recent observations of a polar bear in a zoo spontaneously using tools to access a novel food source. These observations and previously published experiments on brown bears (Ursus arctos) confirm that, in captivity, polar and brown bears are both capable of conceptualizing the use of a tool to obtain a food source that would otherwise not be accessible. Based on the information from all our sources, this may occasionally also have been the case in the wild. We suggest that possible tool use by polar bears in the wild is infrequent and mainly limited to hunting walruses because of their large size, difficulty to kill, and their possession of potentially lethal weapons for both their own defense and the direct attack of a predator. Depuis la fin des années 1700, des signalements d’ours polaires (Ursus maritimus) se servant d’outils (comme des morceaux de glace ou des pierres) pour tuer des morses (Odobenus rosmarus) ont été communiqués verbalement par des guides inuits à divers explorateurs et naturalistes. Les guides en question se fondaient sur les connaissances écologiques traditionnelles (CET) locales de même que sur les interprétations de traces dans la neige ou les récits d’observations directes des chasseurs inuits ayant fait les signalements. Pour évaluer la possibilité que les ours polaires ...